Content validity of reflective mental training cards for student-athletes: a content validation study - Eka Kurnia Darisman; Mulyono; Harwanto; Moh. Hanafi; Gatot Margisal Utomo; Nabilah Azzah Rahmawan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
Mental training plays an important role in supporting athletes’ psychological readiness and performance. However, mental training programs for student-athletes are often conducted informally and lack structured training media that can facilitate reflective learning. This study aimed to examine the content validity of Reflective Mental Training Cards developed for student-athletes. The cards were designed to support psychological skill development through reflective prompts, symbolic illustrations, and key psychological concepts related to sport performance. This study employed a research and development approach focusing on the content validation stage. The implementation involved 15 student-athletes from Universitas PGRI Adi Buana Surabaya who participated in a reflective mental training session using the developed cards. The content validity of the cards was analyzed using Aiken’s V coefficient based on expert evaluation of several aspects, including content relevance to sport psychology concepts, clarity of reflective questions, appropriateness of keywords, suitability of visual illustrations, and practical usability. The results showed that all evaluated aspects achieved high to very high levels of validity, with Aiken’s V coefficients ranging from 0.81 to 0.95. These findings indicate that the Reflective Mental Training Cards are conceptually appropriate and suitable for use as a mental training medium for student-athletes. In conclusion, the developed cards demonstrate strong content validity and have the potential to serve as an innovative tool for facilitating reflective mental training and psychological skill development in university athletes.